Multidisciplinary management of ankyloblepharon filiforme adnatum. Issue 7 (1st July 2020) - Armes, Henry; Williams, Sarah Anne; Dunne, Jonathan; Eccles, Simon James
Abstract : A female infant born at 41+6 weeks via emergency caesarean section due to failure to progress and maternal sepsis was found to have a small fibrous band connecting the upper and lower eyelids of the right eye. This was diagnosed as ankyloblepharon filiforme adnatum. The child was investigated for multisystemic malformations by the paediatric department, but none were found, and the partially fused right eyelid was dissected using microsurgical scissors to allow full opening of the eye. We summarise the management of a rare oculoplastic disorder.